LARGE-SCALE TOPOGRAPHIC MAPPING USING UAV PHOTOGRAMMETRY - Norina Omar; Fauzul Azhan Abdul Aziz; Nurin Uzma Dini Sahrul Nizam (Jurnal Kejuruteraan, Teknologi and Sains Sosial (JKTSS), 2025)
Topographic maps provide essential information for various applications, including infrastructure planning, land surveying, and disaster management. Various methods are available to produce topographic maps, ranging from traditional ground surveying to advanced remote sensing techniques. However, each approach has notable limitations. Ground surveying is time-consuming and labor-intensive, LiDAR systems are often restricted by high costs and operational complexity, and satellite imagery is affected by cloud cover and has lower spatial resolution compared to LiDAR and UAV data. These challenges highlight the need for efficient, accurate, and cost-effective alternatives methods. This study evaluates the effectiveness of UAV photogrammetry in producing large-scale topographic maps by assessing the horizontal and vertical accuracy of orthomosaics and DTMs, as well as analyzing their visual quality. The study site is located at the Ungku Omar Polytechnic, Perak, Malaysia. The DJI Mavic 2 Pro was used to collect digital aerial images, aided by the 3Dsurvey Pilot flight planning apps. Orthomosaics and DTMs were generated using Agisoft Metashape Professional. The findings revealed sub-meter positional accuracy, with RMSEH and RMSEV values of 0.217 m and 0.227 m, respectively. UAVs in conjunction with SfM-MVS photogrammetry may produce reliable and precise topographic mapping, supporting broader adoption of UAV technology in geospatial applications.